Mekanisme Jual Putus Sebelum dan Sesudah Berlakunya Undang-Undang Tentang Hak Cipta dalam Perspektif Pembangunan Ekonomi Nasional di Era Globalisasi - Sudjana Sudjana (Ajudikasi : Jurnal Ilmu Hukum, 2019)
This study aims to determine the enactment of Law Number 28 of 2014 concerning Law No. 19 of 2002 relating to the "Sold Flat" mechanism before and after the enactment of Law Number 28 of 2014 in the Perspective of National Economic Development in the Globalization Era. The research method used is the normative and juridical comparative juridical approach, the specification of analytical descriptive research, the research phase is carried out through the study of literature to examine primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques are carried out through document study, which is done by reviewing documents about positive law. Furthermore, data analysis methods are carried out through qualitative normative. The results of the study show that: (1). the secondary linking point (determinant) of the enactment of Law Number 28 of 2014 concerning Law Number 19 of 2002 based on "Lexus exterior derogat priori" (the new law disregards the old law); (2). The "sold flat" mechanism can be a means of National Economic Development in the Globalization Era if it is supported by consistent law enforcement, adequate facilities, community legal awareness and a conducive legal culture.